KEMISKINAN, PENGANGGURAN DAN KETIDAKADILAN SOSIAL - Roy Charly HP Sipahutar (Institut Agama Kristen Negeri Tarutung, 2019)
Poverty, Unemployment and Social Injustice are classic issues that must always be struggled in every era. This paper seeks to describe our current situation in Indonesia, which is certainly about the three themes. The government's efforts to alleviate poverty have not yet reached a satisfying stage, so that mutual care needs to be taken to improve it. Furthermore, we will also explain how the biblical Christianity view of poverty, unemployment and social injustice that we are facing. And at the end of the article the author will offer how to eradicate unemployment, poverty and realize social justice.BAHASA INDONESIA ABSTRACT: Kemiskinan, Pengangguran dan Ketidakadilan Sosial adalah isu klasik yang harus selalu dipergumulkan dalam setiap era. Tulisan ini berupaya untuk menggambarkan situasi kekinian kita di Indonesia yang tentunya tentang ketiga tema tersebut. Upaya pemerintah untuk mengentaskan kemiskinan belum mencapai tahap yang memuaskan, sehingga perlu kepedulian bersama untuk mempergumulkannya. Selanjutnya akan dipaparkan juga bagaimana pandangan kekristenan yang alkitabiah terhadap Kemiskinan, Pengangguran dan Ketidakadilan Sosial yang sedang kita hadapi. Dan di bagian akhir penulis akan menawarkan bagaimana sebaiknya melakukan pengentasan pengangguran, kemiskinan dan mewujudkan keadilan sosial.Keywords: Poverty, Unemployment, Social Injustice.